Abundance, distribution and diet of the common dolphin, Delphinus delphis, in the northern Aegean Sea (Greece). (25th October 2019) - Milani, Cristina; Vella, Adriana; Vidoris, Pavlos; Christidis, Aristidis; Koutrakis, Emmanouil
Abstract: The abundance, distribution and diet of the short‐beaked common dolphin were investigated as part of the first detailed study on cetacean populations in the North Aegean Sea. Since 2004, the area has been proposed by national and international entities as a marine protected area for common dolphins and other cetacean species owing to its high biodiversity. Abundance and distribution were investigated between 2005 and 2013 through dedicated scientific marine transect surveys, covering 14, 701 km, in sea conditions of Beaufort sea state 3 and below. The line‐transect sampling method was used to estimate relative abundance, using Distance 6.0 software. Encounter rate for this species in the study area was estimated to be 0.24 groups/100 km (1.5 dolphins/100 km), with a mean group size of 6.88 ( SE  = 1.90). Common dolphin sightings were analysed for correlations with eight environmental variables (distance from the coast, depth, slope, median salinity, gradient of salinity, median temperature, gradient of temperature and mean current) using generalized additive modelling. Common dolphin sightings were significantly correlated to depth, temperature and salinity. Stomach‐content analyses were performed on eight suitable samples from common dolphins stranded in the study area. The trophic level of the species was calculated, indicating that this species is a top predator. This research provides the first estimates for abundance and distribution and the first diet analysis for this Mediterranean Endangered dolphin species in the study area based on a year‐round long‐term study.